2008
DOI: 10.1086/589287
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Age and the Manifestations of and Mortality Associated with Severe Malaria

Abstract: Presenting syndromes in severe malaria depend on age, although the incidence and the strong prognostic significance of coma and acidosis are similar at all ages. Age is an independent risk factor for a fatal outcome of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
199
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(223 citation statements)
references
References 21 publications
17
199
6
1
Order By: Relevance
“…One could conclude that culture conditions were not ideal for maintaining the integrity of the EC barrier; however, these results could have an important relevance in severe malaria. Indeed, recent published articles have shown a clear association between acidosis and the prognostic of the disease (Dondorp et al, 2008), mortality being greatest in children where acidosis coexists with impaired consciousness (Maitland and Newton, 2005). These clinical results, compared with the results obtained in our study, suggest that acidosis could be a main factor in BBB breakdown.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…One could conclude that culture conditions were not ideal for maintaining the integrity of the EC barrier; however, these results could have an important relevance in severe malaria. Indeed, recent published articles have shown a clear association between acidosis and the prognostic of the disease (Dondorp et al, 2008), mortality being greatest in children where acidosis coexists with impaired consciousness (Maitland and Newton, 2005). These clinical results, compared with the results obtained in our study, suggest that acidosis could be a main factor in BBB breakdown.…”
Section: Discussionsupporting
confidence: 81%
“…As metabolic acidosis has been described as one of the strongest predictors of a fatal outcome in severe malaria (Dondorp et al, 2008), we decided to test whether the pH of the culture medium could be involved in the permeability enhancement observed. Results show that a decrease in the pH of the culture medium was correlated with an increase in the EC barrier permeability ( Figure 7A).…”
Section: Parasitized Red Blood Cells Metabolism Induces Endothelial Cmentioning
confidence: 99%
“…The literature suggests that the most significant factors leading to death in severe falciparum malaria in adults and children are metabolic acidosis and coma, as well as severely decreased renal function. 27,82,122 P. coatneyi has been reported as causing natural and experimentally induced disease in a variety of NHP species. However, only cynomolgus macaques (M. fascicularis), 33,34,62,74 pig-tailed macaques (Macaca nemestrina), 62 stump-tailed macaques (Macaca arctoides), 98 and Bornean orangutans (Pongo pygmaeus) 84 have been reported to be susceptible to infection in nature, with or without clinical evidence of disease.…”
Section: Ecology Of Nhp Malariasmentioning
confidence: 99%
“…According to research by authors from Germany and Spain, hyperbilirubinemia and hyperparasitemia were most commonly associated severe malaria [21,26]. A multicentric study from Thailand showed that jaundice was present in 529 of 1050 patients (50.4%) with severe malaria and a hyperparasitemia was present in 33.3% [27].…”
Section: Discussionmentioning
confidence: 99%